Preparo, caracterização e aplicação de ferro zero, em escala meso, obtido a partir de cavaco de ferro para degradação de 2,4 e 2,6 dinitrotolueno - Duarte, Ellen de Souza Almeida (2020)
The iron chip is a material from the machining process rich in zero iron andmetal oxides. Due to its high concentration of iron it has a high potential to be used in advanced oxidative processes (POA’s) as a catalytic material. POA's are capable of mineralizing or degrading recalcitrant substances, therefore, the main objective of this work was to evaluate the efficiency of iron chips as a catalytic material in the Fenton process for the treatment of red water, a highly toxic and recalcitrant effluent, produced by the explosives industry and rich in nitroaromatic compounds. In thecharacterization by X-ray diffractometry (XRD) elemental iron and graphite carbon were identified as major constituents and through Dispersive Energy Spectroscopy (EDS) it was possible to observe that the material is composed of 48.3% carbon and 46 , 8% iron. To assist in the study of degradation of nitroatomic compounds that make up red water, a fractional factor planning 33-1was carried out that allowed the optimization of the independent variables used, iron concentration (37.57 g. L-1), peroxide concentration ( 4.06 mM) and pH (3.0). Such parameters led, in a 60-minute treatment, to a degradation of 98% of DNT, a reduction in organic matter of the order of 97% and a significant reduction in acute ecotoxicity indicated for aquatic plants (Lemna minor) and Microcrustaceo (Artemia Salina). It was possible to conclude that the Fenton process assisted by the iron chip was efficient in the degradation of DNT, suggesting that the residue has a high potential to act as a catalytic material in advanced oxidativeprocesses of the Fenton type.